2014
DOI: 10.3174/ajnr.a4160
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Spinal Cord Metastases: Prognostic Value of MRI and Clinical Features from a 13-Year Institutional Case Series

Abstract: BACKGROUND AND PURPOSE:In patients with intramedullary spinal cord metastases, the impact of MR imaging and clinical characteristics on survival has not been elucidated. Our aim was to identify MR imaging and clinical features with prognostic value among patients with intramedullary spinal cord metastases from a large retrospective series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 7 publications
7
15
0
1
Order By: Relevance
“…The interval from primary cancer to ISCM spanned up to 10 years, reminding clinicians of the possibility of ISCM in cancer populations presented with typical neurological deficits and MRI findings, even after a long latency. The thoracic segment appeared to be the most common involved (77.05%), similar to the reports by Diehn et al,9 Rykken et al10 and Payer et al11 Rades and Schiff13 while Findlay et al19 found that the cervical segment was the most common site. Unsurprisingly, lung cancer was the main offender of ISCM, especially the subset of SCLC tending to have ISCM, followed by breast cancer, the same as previous reports 1,2,5,9,10.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The interval from primary cancer to ISCM spanned up to 10 years, reminding clinicians of the possibility of ISCM in cancer populations presented with typical neurological deficits and MRI findings, even after a long latency. The thoracic segment appeared to be the most common involved (77.05%), similar to the reports by Diehn et al,9 Rykken et al10 and Payer et al11 Rades and Schiff13 while Findlay et al19 found that the cervical segment was the most common site. Unsurprisingly, lung cancer was the main offender of ISCM, especially the subset of SCLC tending to have ISCM, followed by breast cancer, the same as previous reports 1,2,5,9,10.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of factors influencing therapeutic activity, ISCM originated from lung/breast carcinomas having a poorer survival than other pathological types. Besides, multiple ISCMs is also a worse prognostic indicator 9. Multiple spinal cord levels involvement and no treatment were unveiled to be poor prognostic factors of OS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cyst and nodule pattern often seen with cerebellar hemangioblastomas may be absent in spinal lesions. Spinal cord metastatic lesions demonstrate variable imaging findings; however, the majority enhance homogeneously with surrounding edema (58).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Das bei zerebellären Hämangioblastomen häufig imponierende zystische oder noduläre Muster kann bei spinalen Tumoren fehlen. Metastasen im Bereich des Rückenmarks sind durch unterschiedliche Bildgebungsmerkmale gekennzeichnet, die meisten zeigen jedoch eine homogene Kontrastmittelanreicherung und ein perifokales Ödem [58].…”
Section: Radiologische Befundeunclassified